Pertanggungjawaban Hukum Bagi Pelaku Tindak Pidana Perdagangan Orang Spa Pijat Sesama Jenis (Homoseksual) Di Kota Medan Dihubungkan Dengan UU Nomer 21 Tahun 2007 Tentang Pemberantasan Tindak Pidana Perdagangan Orang (Studi Kasus : No.3317/Pid.B/2020/Pn.Md - Muhamad Akbar Rafly Astadipura; Chepi Ali Firman (Bandung Conference Series: Law Studies, 2024)
Abstract. Human trafficking has evolved into a more modern form of human trade. One case of human trafficking occurred in Medan City, as in the case of Decision No. 3317/Pid.B/2020/Pn.Mdn. In this case, the modus operandi used for human trafficking was in the form of same-sex spa masseurs (homosexual). The judge's sentence imposed on the defendant was a 3-year prison term and a fine of Rp 120,000,000, or in default, an additional 1-month imprisonment. This is far from the maximum punishment stipulated in Article 2 paragraph (1) of Law Number 21 of 2007 concerning the Eradication of the Criminal Act of Trafficking in Persons, which is 15 years imprisonment and a maximum fine of Rp 600,000. This research aims to determine the legal accountability of perpetrators of the crime of trafficking in persons of the same sex and to identify the forms of legal protection for victims of the crime of human trafficking. The method used by the author is the normative juridical approach. Normative juridical research is an approach to the review of legislation. The accountability of perpetrators of the crime of human trafficking falls into a specific criminal act. If we look at the elements of the actions carried out by the defendant A Meng Als Ko Amin, they violate several provisions related to sexual deviations, illegal efforts such as same-sex massage spas, and most importantly, the crime of human trafficking. Legal protection for victims of human trafficking is contained in Articles 44 to 51, which stipulate the rights granted to victims of the crime of human trafficking. Human trafficking is one of the worst acts that threaten the dignity and humanity of individuals. The form of human trafficking is not only as an object for sexual gratification but has evolved into forms of forced labor, slavery, and other forms such as recruitment, transportation, transfer, harboring, or receipt of persons, by means of threat or use of force, or other forms of coercion, abduction, fraud, deception, abuse of power or vulnerability, giving or receiving payments or benefits to obtain consent from a person in authority over another person, for the purpose of exploitation. Abstrak. Perdagangan orang telah berkembang menjadi bentuk lebih modern dari perdagangan manusia. Salah satu kasus perdagangan orang terjadi di Kota Medan seperti dalam kasus Putusan No. 3317/Pid.B/2020/Pn.Mdn, dalam kasus ini modus perdagangan orang yang digunakan yaitu sebagai pekerja spa pijat sesama jenis (homo seksual). Vonis hakim yang dijatuhkan pada terdakwa yaitu pidana penjara selama 3 tahun dan denda sebanyak Rp 120.000.000,- subs 1 bulan penjara, dimana hal tersebut sangat jauh dari hukuman maksimal yang terdapat didalam Pasal 2 ayat (1) Undang-Undang Nomer 21 Tahun 2007 tentang Pemberantasan Tindak Pidana Perdagangan Orang yaitu 15 tahun penjara dan denda paling banyak Rp 600.000,-. Penelitian ini bertujuan untuk mengetahui pertanggungjawaban hukum terhadap pelaku tindak pidana perdagangan orang sesama jenis dan mengetahui bentuk perlindungan hukum pada korban tindak pidana perdagangan orang. Metode yang penulis gunakan adalah metode pendekatan yuridis normatif. Penelitian yuridis normatif adalah pendekatan pada tinjauan terhadap perundang-undangan. Pertanggungjawaban pelaku tindak pidana perdagangan orang, bahwa hal tersebut masuk kedalam tindak pidana khusus. Jika melihat unsur-unsur perbuatan yang dilakukan oleh terdakwa A Meng Als Ko Amin melanggar beberapa ketentuan dalam ketentuan penyimpangan seksual, usaha illegal berupa spa pijat sesama jenis, dan yang terutama yaitu tindak pidana perdagangan orang. Perlindungan hukum bagi korban tindak pidana perdagangan orang terdapat didalam pasal 44 sampai pasal 51 yang berisi tentang hak-hak korban yang diberikan sebagai korban tindak pidana perdagangan orang. Perdagangan manusia merupakan salah satu tindakan yang paling buruk dalam mengancam harkat dan martabat manusia. Bentuk dari perdagangan orang bukan hanya sebagai objek pemuasan hasrat seksual saja tetapi telah berkembang menjadi bentuk pekerja paksa, perbudakan, dan bentuk lainnya seperti Perekrutan, pengiriman, pemindahan, penampungan, atau penerimaan seseorang, dengan ancaman, atau penggunaan kekerasan, atau bentuk- bentuk pemaksaan lain, penculikan, penipuan, kecurangan, penyalahgunaan kekuasaan atau posisi rentan, memberi atau menerima bayaran atau manfaat untuk memperoleh ijin dari orang yang mempunyai wewenang atas orang lain, untuk tujuan eksploitasi.